Customer Knowledge dan Customer Intimacy: Pengaruhnya Terhadap Repurchase Intention dan Customer Loyalty - Hasnah Rimiyati; Nuryakin (JURNAL ILMIAH EDUNOMIKA, 2026)
This study aims to test a conceptual model and investigate the role of customer intimacy and repurchase intention in the relationship between customer knowledge and customer loyalty with a focus on the study on Islamic banking customers in Indonesia. This study uses a quantitative approach. The sample in this study is Bank Syariah Indonesia customers taken at the Yogyakarta branch service unit. Sampling was done using non-probability sampling with purposive sampling techniques. The number of samples studied was 210 respondents who were customers of Bank Syariah Indonesia. Before conducting data analysis, research instruments are first tested, namely validity and reliability tests, all test results are declared valid and reliable. Data analysis and hypothesis testing using Structural Equation Modelling with AMOS (Amos Graph) software. The results of the study show that customer knowledge has a significant positive effect on customer loyalty, customer intimacy and repurchase intention. Empirical testing in this study also found that customer intimacy had a significant positive effect on repurchase intention and customer loyalty.